STUDY ON THE EFFECT OF ROLLING STRENGTHENING ON THE SURFACE INTEGRITY OF 45 STEEL THREAD ROOT - WANG Dong; LU XinXi; ZHAO JingWen; LIN HongXu; ZHANG Meng (Jixie qiangdu)
The self-made thread root rolling strengthening device based on common lathe CA6140 was used to perform rolling strengthening process on 45 steel thread samples. The surface integrity parameters such as surface roughness, surface microhardness, residual stress and surface microstructure of thread root after rolling were measured by using three-dimensional topography measurement instrument, microhardness tester, X-ray residual stress detector and ultra-depth of field microscope. The effect of rolling strengthening parameters on the surface integrity of thread root was investigated by single factor test. After the 45 steel thread sample underwent the rolling strengthening process, the surface roughness Sa of the thread root is reduced from 1.71 μm to 0.874 μm; the thread root forms an obvious grain refinement layer with a depth of 120 μm; the microhardness increases from 199.3 HV to 379.5 HV, and the hardening degree N=90.4%; the residual stress of the surface layer is distributed in a spoon shape, and the residual stress reaches a peak value of-542 MPa at 105 μm from the surface, and the depth of the residual compressive stress layer can reach 700 μm. The results show that the rolling strengthening process can significantly improve the surface integrity of the thread root, and the rolling depth has the most significant effect.